Women at the beginning : origin myths from the Amazons to the Virgin Mary - Geary, Patrick J., 1948- (Princeton, N.J. : Princeton University Press, 2006)
"In these four essays, Patrick J. Geary explores the way ancient and medieval authors wrote about women. Geary describes the often marginal role women played in origin legends from antiquity until the twelfth century. Not confining himself to one religious tradition or region, he probes the tensions between women in Biblical, Classical, and medieval myths (such as Eve, Mary, Amazons, princesses and countesses), and actual women in ancient and medieval societies. Using these legends as a lens through which to study patriarchal societies, Geary chooses specific moments and texts that best illustrate how the ancient authors (all of whom were male) confronted the place of women in their society."--BOOK JACKET.
Ch. 1. Women and origins in antiquity and the early Middle Ages -- Ch. 2. Writing women out : Amazons and Barbarians -- Ch. 3. A tale of two Judiths -- Ch. 4. Writing women in : sacred genealogy and gender -- Epilogue : women at the end.
Includes bibliographical references (p. [79]-100) and index.
Keywords: Women -- Mythology; Beginning -- Mythology